Practical environmental forensics : - Sullivan, Patrick J. (John Wiley, 2001)
Deals with environmental forensics as the study, analysis, and evaluation of environmental issues in a legal dispute. The authors first introduce the process of environmental forensics, the historical basis of chemical handling and waste management, related laws, and insurance issues. The more technical chapters discuss the forensic application of contaminant transport models, chemical fingerprinting, and risk assessment. Case management, mediation methods for settling cases, and admissibility of evidence are then reviewed. Finally, case studies illustrate how to mitigate damages to clients, allocate damages among responsible parties, and resolve insurance- related issues.